2018
DOI: 10.14419/ijet.v7i3.11.15927
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Net Flow Rate Generation Inside Closed Loop Mechanical Circulatory System Using Impedance Pump

Abstract: This present study focused on the performance of net flow rate inside closed loop mechanical circulatory system with single and double pinching impedance pumps which generates a unidirectional flow of fluid around closed loop of soft viscoelastic tubing. The experimental setup consisted of viscoelastic tubing connected between two ends of rigid tube which was compressed rhythmically or squeezed asymmetrically at various frequencies by motorized pinching. Hence, net flow of fluid around the tubing can occur wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Impedance pump are another term for Liebau effect pumps [6,18,19]. The elastic tube portion is continually subjected to an unequal compression, which might result in wave reflection and unidirectional flow [20]. The experimental investigation of the behaviour of impedance pump shown that flows are extremely responsive to duty cycle and pinching frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Impedance pump are another term for Liebau effect pumps [6,18,19]. The elastic tube portion is continually subjected to an unequal compression, which might result in wave reflection and unidirectional flow [20]. The experimental investigation of the behaviour of impedance pump shown that flows are extremely responsive to duty cycle and pinching frequency.…”
Section: Introductionmentioning
confidence: 99%